Introduction into courtyard buildings in different climates - Taleghani, Mohammad; Tenpierik, Martin; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2014)
This chapter tries to clarify the environmental impacts of a traditional building form which was developed more than 5000 years ago, under the force of harsh hot climates: courtyard building. A courtyard is an outdoor space which is entirely surrounded by buildings or walls. The main purpose is to show if this building form can reduce the energy demand of low- rise residential buildings in order to reduce CO2 emission which generally considered is the main root of climate change. From a literature review on courtyard buildings several climatic aspects of this building form can be extracted. In this step, the paper focuses on the climatic impact(s) in the context of hot-arid, snow, temperate and tropical climates. Results for different configuration of courtyard building, natural elements used in it and situation of openings in different facades are the most important findings of this review paper. The research is limited to considering residential courtyard buildings in four climates; hot- arid, snow, temperate and tropical (based on Koppen-Geiger climate classification). Practical implications—The results of the paper are general climatic characteristics of courtyard buildings. These characteristics can be used for designing new courtyard dwellings. Although the background information of the chapter is based on literature, the innovation is the comprehensive consideration and comparison of environmental characteristics in different climates which has never been done before.